2013
DOI: 10.1371/journal.pone.0069479
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Substitution in the Core Protein of West Nile Virus Increases Resistance to Acidotropic Compounds

Abstract: West Nile virus (WNV) is a worldwide distributed mosquito-borne flavivirus that naturally cycles between birds and mosquitoes, although it can infect multiple vertebrate hosts including horses and humans. This virus is responsible for recurrent epidemics of febrile illness and encephalitis, and has recently become a global concern. WNV requires to transit through intracellular acidic compartments at two different steps to complete its infectious cycle. These include fusion between the viral envelope and the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…Notably, deletions in the N termini of DENV C proteins have been shown to affect virus particle formation (13). In addition, it has recently been shown that amino acid substitutions in the capsid protein of West Nile virus (WNV) can influence the virus' sensitivity to acidotropic compounds, potentially influencing virus infectivity (83). Our data suggest that interactions of NCL with DENV C may also affect the virus particle.…”
Section: Discussionmentioning
confidence: 66%
“…Notably, deletions in the N termini of DENV C proteins have been shown to affect virus particle formation (13). In addition, it has recently been shown that amino acid substitutions in the capsid protein of West Nile virus (WNV) can influence the virus' sensitivity to acidotropic compounds, potentially influencing virus infectivity (83). Our data suggest that interactions of NCL with DENV C may also affect the virus particle.…”
Section: Discussionmentioning
confidence: 66%
“…Besides that, autophagy induced by IR increased by 397% in pSUPER cells, and only by 134% in dCK knock-down cells, suggesting that dCK could increase IR-induced autophagy (Figure 3B). Ammonium chloride (NH4Cl) is a lysosomal inhibitor which can block organelle acidification and enable assessment of autophagic flux [27]. Western blotting revealed that LC3-II increased in a time-dependent manner (Figure 3C), reaching a peak in 72 h with NH4Cl+IR treatment in pSUPER cells, but there was low expression of LC3-II in dCK knock-down cells.…”
Section: Resultsmentioning
confidence: 99%
“…This provides the possibility to investigate the consequences on replicative fitness of the introduction of a single mutation. Accordingly, a large number of genetically defined viral mutants have been constructed to study a variety of flaviviruses, including YFV (Muylaert et al, 1997), DENV (Leardkamolkarn et al, 2010;Matusan et al, 2001), JEV Sumiyoshi et al, 1995;Ye et al, 2012;Zhao et al, 2005), WNV (Arroyo et al, 2004;Martin-Acebes et al, 2013;Van Slyke et al, 2012) or TBEV (Gritsun et al, 2001;Mandl et al, 2000;Yoshii et al, 2004).…”
Section: Studying Point Mutationsmentioning
confidence: 99%